Public Services Versus Covid-19: Participation of Villagers in Public Service based on E-Government in Pandemic - Eko Mukminto; Martitah Martitah; Ratih Damayanti; Bayangsari Wedhatami (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2023)
This article aims to show how to improve public services' capability and accessibility through e-government for villagers to reduce the rate of spread and infection of Covid-19 and as community participation in alternative ways of getting public services, Electronic Government (e-Gov) or digital government exists. Electronic government (e-Gov) itself provides information and public services, business affairs, services related to governance, et cetera by using information technology tools. However, the obstacles in this e-government-based public service are in applying the information system and the knowledge and access to information on this e-government-based public service. The digital divide is found in rural communities, often uninformed and reluctant to experience new technologies. Therefore, a community service program is needed, namely Improving Community Capability and Accessibility in Utilizing E-Government Public Services for villagers in the Middle of the COVID-19 Pandemic Outbreak in Semarang Regency.